Memorandum of understanding between Universiti Teknologi MARA and University of Santo Tomas / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2020)
The purpose of this MoU is to develop academic and educational cooperation on the basis of mutual and reciprocity and to promote relations and mutual understanding between universities.